Ecological Interface Design: Sensor Failure Diagnosis in Air Traffic Control. Issue 19 (2016) - Bijsterbosch, V.A.; Borst, C.; Mulder, M.; van Paassen, M.M.
Abstract: Future air traffic control will have to rely on more advanced automation in order to support controllers in their job of safely controlling increased traffic volumes. A prerequisite for the success of such automation is that the underlying data driving it is reliable. Current technology, however, still warrants human supervision in coping with (data) uncertainties and consequently in judging the validity of machine decisions. In this paper the Ecological Interface Design (EID) framework is explored to assist controllers in fault diagnosis using a prototype ecological interface (called the Solution Space Diagram) for tactical conict detection and resolution in the horizontal plane. Results from a human-in-the-loop experiment with sixteen participants indicate that the ecological interface with explicit presentation of the means-ends relations between higher-level functional goals and lower-level physical objects (i.e., aircraft) enables improved sensor failure detection. Especially in high complexity scenarios, this feature had a positive impact on failure detection performance.